Cognitive variability in bipolar II disorder: who is cognitively impaired and who is preserved. (26th April 2016) - Solé, Brisa; Jiménez, Esther; Torrent, Carla; del Mar Bonnin, Caterina; Torres, Imma; Reinares, María; Priego, Ángel; Salamero, Manel; Colom, Francesc; Varo, Cristina; Vieta, Eduard; Martínez‐Arán, Anabel
Abstract : Objectives: Although it is well established that euthymic patients with bipolar disorder can have cognitive impairment, substantial heterogeneity exists and little is known about the extent and severity of impairment within the bipolar II disorder subtype. Therefore, the main aim of this study was to analyze cognitive variability in a sample of patients with bipolar II disorder. Methods: The neuropsychological performance of 116 subjects, including 64 euthymic patients with bipolar II disorder and 52 healthy control subjects, was examined and compared by means of a comprehensive neurocognitive battery. Neurocognitive data were analyzed using a cluster analysis to examine whether there were specific groups based on neurocognitive patterns. Subsequently, subjects from each cluster were compared on demographic, clinical, and functional variables. Results: A three‐cluster solution was identified with an intact neurocognitive group (n = 29, 48.3%), an intermediate or selectively impaired group (n = 24, 40.0%), and a globally impaired group (n = 7, 11.6%). Among the three clusters, statistically significant differences were observed in premorbid intelligence quotient (p = 0.002), global functional outcome (p = 0.021), and leisure activities (p = 0.001), with patients in the globally impaired cluster showing the lowest attainments. No differences in other clinical characteristics were found among the groups. Conclusions: These results confirm that neurocognitive variability is also present among patients with bipolar II disorder. Approximately one‐half of the patients with bipolar II disorder were cognitively impaired, and among them 12% were severely and globally impaired. The identification of different cognitive profiles may help to develop cognitive remediation programs specifically tailored for each cognitive profile.